Efektivitas EDTA (Ethylenediaminetetracetic Acid) dalam Meningkatkan Akumulasi Timbal pada Saccharum spontaneum yang Ihmbuh di Limbah Penambangan Emas - Hidayati, Nuril; Juhaeti, Titi; Syarif, Fauzia (Perhimpunan Biologi Indonesia, 2006)
ABSTRACTEffectivity of EDTA (EthylenediaminetetraceticAcid) in Increasing Lead Accumulationof Saccharum spontaneum Grown Under Gold Mine Waste. Lead (Pb) isknown as one of a major metal contaminant in mine tailing. This metal has low solubility,and in many cases, is not readily available. In most soils capable of supporting plantgrow, the soluble Pb2+ levels are relatively low and will not promote substantial uptake bythe plant. In addition, many plants retain Pb2+ in their roots with only minimal trabsportto the aboveground plant portions. Therefore, it is important to find ways to enhance thebioavailability of Pb2+ or to find specific plants that can better translocate the Pb2+ intoharvestable portions for phytoremediation. The success of Pb phytoremediation is tohave significant Pb availability as well as a large quantity of plant biomass with high rateof growth. This experiment was conducted to obtain both purposes. Saccharumspontaneum which proven tolerant and dominant in contaminated area as well as potentialin producing high biomass was used in this research.The plants were grown in wastemedia added by 100 ppm, 200 ppm and 300 ppm of Pb. Ethylenediaminetetracetine Acid(EDTA) was applied to increase Pb availability and plant uptake as well as translocationto the aboveground portions. The results showed that the plant still capable of growingunder the highest level of Pb. EDTA increase Pb availability and plant uptake. Pb accumulationin the aboveground biomass of EDTA treated plants were relatively higher thanuntreated plants.Key words: Timbal, EDTA, phytoremediation